Blind docking methods have been inappropriately used in most network pharmacology analysis - Che, Xinhao; Zhang, Lei (Frontiers in Pharmacology, 2025)
Network pharmacology methods have bridged the gap between traditional Chinese medicine (TCM) theory and contemporary pharmacological research and have been widely used in the study of multi-component, multi-target mechanisms of action of TCM. Molecular docking in silico is typically used after network analysis to validate the binding between protein targets and active components of TCM. However, unreasonable docking methods, especially the abuse of blind docking, have raised doubts about the docking results. This paper expresses concern about the above phenomenon based on a comprehensive assessment of the accuracy of the blind docking methods and calls for the correct use of docking methods to make the results of network analysis and experiments more convincing.